The Impact of Occupational Stress on Job Burnout Among Bank Employees in Pakistan, With Psychological Capital as a Mediator - Khalid, Arslan; Pan, Fang; Li, Ping; Wang, Wei; Ghaffari, Abdul Sattar (Frontiers in Public Health, 2020)
Background: Job burnout is a major issue for workers in the banking sector. Many employees report feeling exhausted and want to leave their jobs due to the extra pressure and workload from their superiors and clients. They also report not being well compensated for their hard work, which they believe they do to provide the best service to their clients. Methods: A cross-sectional study was made in various banks in different cities of Pakistan. An adapted questionnaire, including the effort-reward imbalance scale, psychological capital, and Maslach burnout inventory general survey were used to collect data from 1,778 male and female bank employees. Results: There was a significant and positive relationship between extrinsic effort and over-commitment on the one hand, and emotional exhaustion and depersonalization on the other. It was also found that reward was negatively associated with emotional exhaustion and depersonalization. However, reward had a positive association with personal accomplishment. There was a gender difference in the mediating effect of psychological capital on stress at work and job burnout. Conclusion: Male attitudes to work tend to be motivated by reward and appreciation, whereas females tend to demand a better working environment. To reduce job, burnout suitable interventions could be introduced for bank employees, whilst management support plays an important role in increasing or decreasing stress in employees.